Coordinating mind and movement : exploring parallels between the F.M. Alexander technique and ‘the new approach to violin playing' - Louw, Maria Christina (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MMus (Music))--University of Stellenbosch, 2004.